Pengaruh Persepsi, Kualitas SDM dan Sosialisasi Terhadap Penerapan SAK EMKM Pada Laporan UMKM Di Kota Batam - Lai Juniawati; Efriyenti, Dian (SCIENTIA JOURNAL, 2024)
This research aims to ascertain the impact of Perception, Quality of Human Resources (HR), and Socialization on the implementation of SAK EMKM in the financial statements of MSMEs in Batam City. For this study, the sample was drawn from 875 entities registered at the Office of Cooperatives and Micro Enterprises through purposive sampling, resulting in 151 samples. The data utilized in this study originates from primary data collected via the distribution of questionnaires using the Slovin formula. According to the test outcomes of this study, it is concluded that Perception significantly influences the application of SAK EMKM, Human Resources Quality significantly influences the application of SAK EMKM, and Socialization also plays a significant role in the application of SAK EMKM. Simultaneously, Perception, Quality of Human Resources, and Socialization collectively wield a significant influence on the application of SAK EMKM. The coefficient of determination indicates that 59.3% of the application of SAK EMKM is influenced by the independent variables tested in this study, while the remaining 40.7% is impacted by other variables not examined in this research.